Social Studies Needs (New) White People: The Case for Including Allies in the Curriculum. Issue 4 (4th July 2018) - Smith, William L.; Crowley, Ryan M.
Abstract: In this conceptual article we consider the pedagogical possibilities and pitfalls of incorporating White ally figures in history and social studies curricula. Drawing on the burgeoning scholarship on race and the social studies and literature on alternative racial orientations, such as allies, antiracists, and abolitionists, we contend that educators can use White-ally pedagogy to offer White students, in particular, examples of an antiracist White racial identity. We close with guidelines to provide social studies educators and teacher educators with a starting point for effectively introducing White allies into the social studies.